2023
DOI: 10.1111/cobi.14052
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges for Common Agricultural Policy reform to support the European Green Deal

Abstract: The Common Agricultural Policy (CAP) is the European Union's main instrument for agricultural planning, with a new reform approved for 2023-2027. The CAP intends to be aligned with the European Green Deal, a set of policy initiatives underpinning sustainable development and climate neutrality in the EU, but several flaws cast doubts about the compatibility of the objectives of these two policies. We reviewed recent literature on the potential of CAP environmental objectives for integration with the Green Deal:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…In light of the ongoing emphasis on sustainable agricultural practices in the European Union [127], the integration of vermicomposting into governmental strategies has shown potential to address several environmental challenges while fostering agricultural resilience [128]. Vermicomposting aligns seamlessly with government policies and frameworks, such as the European Green Deal, that promote the transition to a circular economy and mitigate the environmental footprint of various industries, including viticulture [129]. Governments can effectively address several pressing concerns by incorporating vermicomposting into these strategies, including the management of organic waste generated by the vine and wine industry, the restoration of soil health and fertility through the use of nutrient-rich vermicomposts instead of chemical fertilizers, and an overall reduction in greenhouse gas emissions associated with conventional waste disposal methods.…”
Section: Vermicomposting As a Strategy To Valorize Vine And Wine By-p...mentioning
confidence: 99%
“…In light of the ongoing emphasis on sustainable agricultural practices in the European Union [127], the integration of vermicomposting into governmental strategies has shown potential to address several environmental challenges while fostering agricultural resilience [128]. Vermicomposting aligns seamlessly with government policies and frameworks, such as the European Green Deal, that promote the transition to a circular economy and mitigate the environmental footprint of various industries, including viticulture [129]. Governments can effectively address several pressing concerns by incorporating vermicomposting into these strategies, including the management of organic waste generated by the vine and wine industry, the restoration of soil health and fertility through the use of nutrient-rich vermicomposts instead of chemical fertilizers, and an overall reduction in greenhouse gas emissions associated with conventional waste disposal methods.…”
Section: Vermicomposting As a Strategy To Valorize Vine And Wine By-p...mentioning
confidence: 99%
“…The aspiration under the European Green Deal activities is to reduce the use of not only mineral fertilizers, but also antibiotics and pesticides [55]. The use of enzymes such as dehydrogenases may contribute to effective soil monitoring and designing appropriate cultivation strategies to ensure environmental safety and financial security for farmers [29,30,57]. With the use of biological and physicochemical parameters, this can become the basis for long-term research to control and monitor the condition of soils and verify suggested solutions to improve the natural and agricultural environment.…”
Section: Soil Enzymatic Activitymentioning
confidence: 99%
“…More recent studies have emphasized the importance of harmonizing CAP policies with the EU's climate and biodiversity aspirations [145,146] while accentuating the imperative to integrate environmental and climate objectives into the CAP to ensure its contribution to the EGD's objectives [147,148]. Academic research has also emphasized the necessity of dovetailing the CAP with the Sustainable Development Goals established by the UN [147].…”
Section: The Latent Shift Toward New Environmental Targetsmentioning
confidence: 99%
“…More recent studies have emphasized the importance of harmonizing CAP policies with the EU's climate and biodiversity aspirations [145,146] while accentuating the imperative to integrate environmental and climate objectives into the CAP to ensure its contribution to the EGD's objectives [147,148]. Academic research has also emphasized the necessity of dovetailing the CAP with the Sustainable Development Goals established by the UN [147]. Specifically, the pertinence of Goal 2, which aims at reducing hunger, attaining food security, enhancing nutrition, and fostering sustainable agriculture, is of critical significance from this perspective [149,150].…”
Section: The Latent Shift Toward New Environmental Targetsmentioning
confidence: 99%